2021
DOI: 10.1097/qmh.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Adoption of Electronic Decision Support Tools for Preeclampsia Management

Abstract: Background: Electronic health record (EHR)–based clinical decision support tools can improve the use of evidence-based clinical guidelines for preeclampsia management that can reduce maternal mortality and morbidity. No study has investigated the organizational capabilities that enable hospitals to use EHR-based decision support tools to manage preeclampsia. Objective: To examine the association of organizational capabilities and hospital adoption of EHR-based decision support tools for preeclampsia manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[11][12][13] Second, we examined whether hospital processes to disseminate best practices were associated with the use of BH care processes, as prior evidence observed that hospitals with processes to disseminate best-care practices were more likely to use clinical decision support tools to enhance care in other clinical domains. 14 Third, based on evidence on the importance of innovation capacity in relation to other upstream care strategies, 15 we examined whether barriers to innovation may impede the implementation of new processes like BH care in the ED. Last, we examined the hospital capacity to treat BH conditions based on the presence of designated beds for psychiatric or substance use disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Second, we examined whether hospital processes to disseminate best practices were associated with the use of BH care processes, as prior evidence observed that hospitals with processes to disseminate best-care practices were more likely to use clinical decision support tools to enhance care in other clinical domains. 14 Third, based on evidence on the importance of innovation capacity in relation to other upstream care strategies, 15 we examined whether barriers to innovation may impede the implementation of new processes like BH care in the ED. Last, we examined the hospital capacity to treat BH conditions based on the presence of designated beds for psychiatric or substance use disorders.…”
mentioning
confidence: 99%
“…First, because recent studies have found that hospitals using quality improvement methods were more likely to adopt care delivery innovations, we examined associations between BH care processes and hospital use of Lean, Six Sigma, or Robust Performance Improvement 11–13 . Second, we examined whether hospital processes to disseminate best practices were associated with the use of BH care processes, as prior evidence observed that hospitals with processes to disseminate best-care practices were more likely to use clinical decision support tools to enhance care in other clinical domains 14 . Third, based on evidence on the importance of innovation capacity in relation to other upstream care strategies, 15 we examined whether barriers to innovation may impede the implementation of new processes like BH care in the ED.…”
mentioning
confidence: 99%